Banking Soundness: Comparison between Conventional and Sharia Banking in Indonesia - Musdholifah, Musdholifah; Hartono, Ulil (International Journal of Economics and Financial Issues, 2018)
Banking is a business sector which has an important role in the economy. As an intermediary institution between the excess and needy funds, the role of banking in the payment traffic becomes very important. Banking soundness should always be control, so as not to bring negative impact on the whole economy. Economists argue that problems in the banking can cause problems in other industries. This study aims to assess banking financial stability both of conventional and Sharia banks with Crisis and Default Index (CD Index). CD Index assesses the vulnerability of the bank has difficulty (crisis) with four sides of the assessment are funding risks, credit risk, investment risk, and exchange rate risk. In addition, this study also using a macroeconomic and internal bank as a variable to the identification of banking financial stability. The results showed that during the period 2012 and 2015 are the best period for conventional banks because at that time only a few banks indicated the crisis, while for Sharia banks the period 2011 and 2013 which is the best period. For the conventional bank variables are CAR and NPL have a positive effect, while LCOST, ROA, and LDR have a negative effect on banking soundness. For Sharia banks, variables are LCOST and BOPO which positive affecting to banking soundness. Keywords: Banking Soundness, CD Index, Conventional Bank, Sharia Bank JEL Classifications: F45, G2, H12